2020
DOI: 10.1108/jhtt-05-2019-0081
|View full text |Cite
|
Sign up to set email alerts
|

How can gamification contribute to achieve SDGs?

Abstract: Purpose Ecogamification can make a positive impact on Tourism. With this in mind, the present study aims to examine specific stakeholders – those positioned at the upstream side of gamification process – and their perspectives concerning not only the benefits, but also the challenges of (eco)gamification. Design/methodology/approach The study follows a qualitative-exploratory approach and bases its results on the analysis of 10 in-depth interviews conducted with buyers and providers from the emerging Portugu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 33 publications
(44 reference statements)
0
7
0
1
Order By: Relevance
“…Gamification is being utilized to work towards and achieve humanity's SDGs. Souza et al [20] suggested that using gamification to develop programs may help to alleviate some of the environmental damage that is caused by overtourism.…”
Section: Discussionmentioning
confidence: 99%
“…Gamification is being utilized to work towards and achieve humanity's SDGs. Souza et al [20] suggested that using gamification to develop programs may help to alleviate some of the environmental damage that is caused by overtourism.…”
Section: Discussionmentioning
confidence: 99%
“…Competitive games allow people to compete against one another to achieve high game results while also satisfying relationship needs (Suh et al, 2017). Gamification is the design of a virtual system that motivates users by providing them with a game‐like experience (Koivisto & Hamari, 2019; Souza et al, 2020). It is the use of a game design to entice people to participate in non‐gaming activities (Deterding et al, 2011; Xue et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, it associates conservation aspects as virtual and recreational dynamics can be generated, with the use of virtual or augmented reality, for example, allowing the history of the place to be known, making it more accessible, and continuing to preserve its integrity [41]. Sustainability concepts are integrated by promoting more environmentally friendly tourism, generating tourism options that reduce travel and waste generation or the direct impact on some natural environments [33], as well as the association of the Sustainable Development Goals as a guide for the promotion of economic development in the region, [39].…”
Section: Spainmentioning
confidence: 99%